E-Waste Management in Nam Theun 2 Power Company Limited: A Review of Issues, Challenges and Solutions: https://doi.org/10.69692/SUJMRD0901338 - Keovongsa, Souttiphong; Phonhalath, Keophousone; Phommixay, Sengthavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This paper reviews the e-waste management practices of Nam Theun 2 Power Company (NTPC), one of the leading power generation companies in Laos. The study focuses on the company's use of Total Environmental Solutions – Asset Material Management (TES-AMM), a leading e-waste recycling company, to manage their e-waste. In this paper, a mixed-methods research design has been applied, including a survey of employees and interviews with key stakeholders at NTPC, as well as document analysis to assess the company's compliance with the relevant regulations and standards. The results of the study indicate that NTPC has an effective e-waste management system in place that is compliant with the relevant regulations and standards, but it also highlights opportunities for improvement. The study also provides an overview of TES-AMM's e-waste recycling process, which is found to be in line with international standards. The study contributes to the existing literature by providing insights into the specific challenges and opportunities for improving e-waste management in the power generation industry part in Laos.